Process Improvement of Rotary Kiln (RK) Technology with Electric ARC Furnace (EAF) at PT Sebuku Iron Lateritic Ores Using a Technometric Approach - Koko Srihandoko; Udisubakti Ciptomulyono; Maranatha Wijayaningtyas (Publikasi Indonesia, 2025)
This study aims to assess the contribution of RK and EAF technologies using a technometric approach, focusing on four technological components: Technoware, Humanware, Inforware, and Orgaware (THIO). Furthermore, the study analyzes the economic feasibility of both systems using financial indicators and sensitivity risk analysis. The methodology includes calculating the Technology Contribution Coefficient (TCC) for each technology based on the degree of sophistication, state of the art, and intensity of use. Additionally, the economic analysis employs indicators such as Net Present Value (NPV), Internal Rate of Return (IRR), Benefit-Cost Ratio (B/C Ratio), and Payback Period, along with sensitivity analysis on cost and interest rate variables. The results show that both technologies fall into the semi-modern category, with TCC values of 0.7588 for RK and 0.7563 for EAF. However, Humanware in RK and Inforware in EAF are identified as the weakest contributing components, highlighting priority areas for improvement. From an economic perspective, EAF outperforms RK across all financial indicators under both optimistic and pessimistic scenarios. These findings lead to a recommendation for a gradual transformation from RK to EAF, emphasizing workforce development, information system digitization, and technological management enhancement. The primary output of this research is the development of a technology contribution assessment model based on technometric analysis, integrated with economic feasibility evaluation, providing a strategic foundation for more precise technology and investment decision-making in the mineral processing industry.